The Infection, Coinfection, and Abundance of Intestinal Protozoa Increase the Serum Levels of IFABP2 and TNF-α in Patients With Rheumatoid Arthritis - Guzmán-Guzmán, Iris Paola; Nogueda-Torres, Benjamín; Zaragoza-García, Oscar; Navarro-Zarza, José Eduardo; Briceño, Olivia; Pérez-Rubio, Gloria; Falfán-Valencia, Ramcés; Gutiérrez-Pérez, Ilse Adriana; Parra-Rojas, Isela (Frontiers in Medicine, 2022)
Protozoa, nematodes, and platyhelminthes are of clinical interest due to their role on the modulation of the immune responses. To determine the frequency of infection by intestinal parasites as well as the status of single or mixed infection (co-infection) and its relation with inflammation and intestinal permeability markers in rheumatoid arthritis (RA) patients. A cross-sectional study was conducted in 18 women diagnosed with RA. A fecal sample of each participant was analyzed for parasitic identification. The DAS28-ESR score was determined as well as the serum levels of TNF-, IL-10, IL-17A and the intestinal fatty-acid binding protein 2 (IFABP2) through the ELISA technique. The T CD4+ and CD8+ lymphocytes’ proportions were determined by flow cytometry. In this study, 50% (n = 9) of the total sample tested were positive to the presence of intestinal protozoa (27% by single infection and 22.2% by co-infection). Blastocystis sp. and Endolimax nana were the most frequently identified protozoa. The serum levels of IFABP2 were increased in patients with infection by protozoa, mainly in those individuals with co-infection and a larger abundance of Blastocystis sp. We found that being co-infection by protozoa was related to higher levels of TNF- and higher frequency of T CD4+ lymphocytes, mainly in patients under anti-rheumatic treatment. Infection by intestinal protozoa is associated with increased intestinal permeability in RA patients, thus infection, co-infection, and abundance of intestinal protozoa should be clinically screened because they could be an associated factor to the clinical variability of the disease.